First estimates of diffuse gastric cancer risks for carriers of CTNNA1 germline pathogenic variants. Issue 12 (29th August 2022) - Coudert, Marie; Drouet, Youenn; Delhomelle, Hélène; Svrcek, Magali; Benusiglio, Patrick R; Coulet, Florence; Clark, Dana Farengo; Katona, Bryson W; van Hest, Liselotte P; van der Kolk, Lizet E; Cats, Annemieke; van Dieren, Jolanda M; et al.
Abstract : Background: Pathogenic variants (PV) of CTNNA1 are found in families fulfilling criteria for hereditary diffuse gastric cancer (HDGC) but no risk estimates were available until now. The aim of this study is to evaluate diffuse gastric cancer (DGC) risks for carriers of germline CTNNA1 PV. Methods: Data from published CTNNA1 families were updated and new families were identified through international collaborations. The cumulative risk of DGC by age for PV carriers was estimated with the genotype restricted likelihood (GRL) method, taking into account non-genotyped individuals and conditioning on all observed phenotypes and genotypes of the index case to obtain unbiased estimates. A non-parametric (NP) and the Weibull functions were used to model the shape of penetrance function with the GRL. Kaplan-Meier incidence curve and standardised incidence ratios were also computed. A 'leave-one-out' strategy was used to evaluate estimate uncertainty. Results: Thirteen families with 46 carriers of PV were included. The cumulative risks of DGC at 80 years for carriers of CTNNA1 PV are 49% and 57%, respectively with the Weibull GRL and NP GRL methods. Risk ratios to population incidence reach particularly high values at early ages and decrease with age. At 40 years, they are equal to 65 and 833, respectively with the Weibull GRL and NP GRL. Conclusion: This is the largest series of CTNNA1 families that provides the first risk estimates of GC. These data will help to improve management and surveillance for these patients and support inclusion of CTNNA1 in germline testing panels.